Rational molecular design of PEOlated ladder-structured polysilsesquioxane membranes for high performance CO2 removal - Park, Sunghwan; Lee, Albert S.; Do, Yu Seong; Hwang, Seung Sang; Lee, Young Moo; Lee, Jung-Hyun; Lee, Jong Suk (ROYAL SOC CHEMISTRY, 2015)
Poly(methoxy(polyethyleneoxy)propyl-co-methacryloxypropyl)silsesquioxane membranes with different copolymer ratios were successfully fabricated via UV-induced crosslinking with mechanical stability. By selectively introducing polyethylene oxide (PEO) groups covalently bound to the ladder-structured polysilsesquioxane, we effectively suppressed the PEO crystallization, allowing for excellent CO2/H-2 and CO2/N-2 separation under single as well as mixed gas conditions.
Keywords: GAS-PERMEATION PROPERTIES; POLY(ETHYLENE OXIDE); CARBON-DIOXIDE; HYDROGEN PURIFICATION; POLYETHER DIAMINE; BLOCK-COPOLYMERS; HYBRID MEMBRANES; FREE-VOLUME; SOLUBILITY; SEPARATION